Pension Power : Unions, Pension Funds, and Social Investment in Canada - Carmichael, Isla (Book collections on Project MUSE., 2005)
"In Pension Power, Isla Carmichael argues that unions could - and should - have a new role to play in the economy by gaining control over their members' pension funds. She demonstrates how the financial industry's access to the capital goes against the interests of working people, and she provides convincing evidence that management of pensions by unions would offer better protection of employee benefits and greater investment in community infrastructure and the environment."--Jacket